考虑时变刚度的齿轮振动响应仿真分析 - 叶盛鉴; 张帆; 尹逊民; 张超 (Jixie chuandong)
The solid model of gear transmission system is established by MASTA,and the finite element analysis of the gear transmission system stiffness is carried out by ANSYS packages under MASTA environment.As an excitation source of response analysis of the gear box,the transmission error（TE） caused by time-varying stiffness is calculated.The affect of time-varying stiffness to the vibration of the gear box is analyzed by ANSYS.This method can be used for analyzing and evaluating the vibration and noise of the gearbox.